Comparative evaluation of internal fit and marginal gap of endocrowns using lithium disilicate and polyether ether ketone materials - an in vitro study - Nermeen Nagi; Ahmed Mahmoud Fouda; Christoph Bourauel (BMC, 2023)
Abstract Background The aim of the study was to investigate the effect of material and occlusal preparation design on the internal fit and marginal gap of endocrowns made of Polyether ether ketone (PEEK) and lithium disilicate. Methods 32 endocrowns were fabricated on prepared mandibular molars and divided into two groups (n = 16) according to the material. Group L: lithium disilicate and Group P: PEEK. Each group was further subdivided into two subgroups (n = 8) according to the occlusal preparation design: full occlusal coverage (LF and PF) and partial occlusal coverage (LP and PP). Samples were analyzed using microcomputed tomography (µCT) with a voxel size of 6 μm to evaluate internal fit, and an optical microscope was used to evaluate the marginal gap. Data were collected, tabulated, and statistically analyzed. Numerical data were described as mean and standard deviation and compared using the ANOVA test. The level of significance was set at α P ≤ 0.05. Results All groups' internal fit and marginal gaps values were within the acceptable clinical range. However, the lithium disilicates group recorded statistically significantly higher mean internal gap values than the PEEK groups. Regardless of the material, the difference between the two occlusal designs was not statistically significant in both internal fit and marginal gap records. Conclusion Within the limitations of this study, PEEK endocrown restorations revealed better internal fit and marginal gap than lithium disilicate endocrown restorations. The marginal and internal fit of both lithium disilicate and PEEK endocrown restorations were within the clinically acceptable range. The occlusal preparation design had no influence on the internal fit and marginal gap of the endocrown restoration.